1994
DOI: 10.1021/jo00099a012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of a Bis-arborol-Tetrathiafulvalene Gel: Toward a Self-Assembling "Molecular" Wire

Abstract: A gel-forming compound, 4,4'-bis[[N,"-bis[2-hydroxy-l,l-bis( hydroxymethyl)ethyl]-7,7-diamidoheptyl]thio]-5,5'-dimethyltetrathiafulvalene (1) has been prepared, with the aim of manufacturing a self-assembling "molecular" wire. The gel has been characterized structurally by optical and atomic force microscopy. These investigations revealed stringlike superstructures with lengths of the order of microns and diameters ranging from about 30 to several hundred nanometers. Absorption spectroscopy of 1, both in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 0 publications
0
63
0
4
Order By: Relevance
“…[61][62][63][64][65] The self-assembled molecular wires of a TTF gel (24, Scheme 7) was introduced in 1994 by Jørgensen and coworkers. [66] Bryce et al have reported the first experimental demonstration of a conductive TTF gel using spin-coated films of 25.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63][64][65] The self-assembled molecular wires of a TTF gel (24, Scheme 7) was introduced in 1994 by Jørgensen and coworkers. [66] Bryce et al have reported the first experimental demonstration of a conductive TTF gel using spin-coated films of 25.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…[ [66][67][68][69][70][71][72] Organic Electronics Angewandte Chemie behavior with a conductivity of 10 S cm À1 whereas 31 showed five times less conductivity when doped. The advantage of the hybrid system is that the mixed-valent donor stacks attain a highly conducting b phase without any heat treatment, immediately after doping.…”
Section: Angewandte Minireviewsmentioning
confidence: 99%
“…[4] TTFs can also form fibrous aggregates as a result of hydrophobic interactions in regions of their molecular structure, [5] through stacking interactions, [6] and during the formation of Langmuir layers. [7] Hydrogen bonds can be used to influence the disposition of TTF units in crystals; [8] for example, hydrogen bonds to amide groups have been shown to aid the formation of stacks of molecules.…”
mentioning
confidence: 99%
“…In the solid state, hydrogen bonds have been used to influence the disposition of TTF units with varying degrees of success, [41][42][43][44][45][46][47] one example being that of amide bonds which aid the formation of stacks of molecules. [48] On the other hand, fibres have been formed in Langmuir films [49,50] and gels [51] with a random orientation, and gels of TTFs have shown some alignment of the fibres. [52] In two cases xerogels based on TTF derivatives have been proven to conduct electricity.…”
Section: Introductionmentioning
confidence: 99%